A new paradigm for international uniform substantive law conventions. (3rd September 2019) - Ferrari, Franco
Abstract: This paper posits that a paradigm shift has taken place in respect of the way the relationship between private international law and international uniform law conventions is understood. The author shows that recent international uniform law conventions evidence that their drafters do not consider the relationship to be an antagonistic one, but rather one of symbiosis.